2021
DOI: 10.1029/2020jc016315
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stratification and Yucatan Current Transport on the Loop Current Eddy Shedding Process

Abstract: The Loop Current System (LCS), composed by the Loop Current (LC) and the Loop Current Eddies (LCEs), constitutes the main circulation pattern and source of variability in the Gulf of Mexico (GoM; NASEM, 2018). The LCS plays a key role in the region by determining its climate and weather (Oey et al., 2005; Schmitz et al., 2005), and by affecting all the economic activities in the region (Yoskowitz et al., 2013). The LC originates in the Yucatan Channel as the Yucatan Current (YC), where it enters the GoM formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…To forecast and visualize the evolution and fate of different oil spill scenarios at pre-defined locations, we employ several international operational models: the HYbrid Coordinate Ocean Model (HYCOM), the Regional Ocean Modeling System (ROMS), the Nucleus for European Modelling of the Ocean (NEMO), the Navy Coastal Ocean Model (NCOM), the Global Forecasting System model (GFS, NCEI-NOAA), and the Weather Research and Forecasting (WRF) and WRF-Chem for the atmosphere and WAVEWATCHIII for waves. An analysis of the differences and similarities among the modeling results has helped us understand their capabilities and guided their use for development of an ensemble-based system to generate oil spill scenarios and a probabilistic forecast system (Meza-Padilla et al, 2019;Duteil et al, 2019;Gómez-Valdivia and Parés-Sierra, 2020;Mazlo et al, 2020;Moreles et al, 2020;Guerrero et al, 2020;Damien et al, 2021). These et al, 2021).…”
Section: Hydrocarbon Spillsmentioning
confidence: 99%
“…To forecast and visualize the evolution and fate of different oil spill scenarios at pre-defined locations, we employ several international operational models: the HYbrid Coordinate Ocean Model (HYCOM), the Regional Ocean Modeling System (ROMS), the Nucleus for European Modelling of the Ocean (NEMO), the Navy Coastal Ocean Model (NCOM), the Global Forecasting System model (GFS, NCEI-NOAA), and the Weather Research and Forecasting (WRF) and WRF-Chem for the atmosphere and WAVEWATCHIII for waves. An analysis of the differences and similarities among the modeling results has helped us understand their capabilities and guided their use for development of an ensemble-based system to generate oil spill scenarios and a probabilistic forecast system (Meza-Padilla et al, 2019;Duteil et al, 2019;Gómez-Valdivia and Parés-Sierra, 2020;Mazlo et al, 2020;Moreles et al, 2020;Guerrero et al, 2020;Damien et al, 2021). These et al, 2021).…”
Section: Hydrocarbon Spillsmentioning
confidence: 99%
“…The renewed interest in thermodynamically-active rotating shallow-water modeling 5,6,13,15,20,35,[71][72][73][74] motivated this work, which presented extended rotating shallow-water theories with thermodynamics and geometry. With a focus on the ocean mixed-layer, the topmost part of the ocean, a general model was introduced and interpreted as such, considering in addition several submodels, ranging from the shallow-water equations themself.…”
Section: B the Il 0+ Modelmentioning
confidence: 99%
“…This paper is motivated by renewed interest 5,6,13,15,20,35,[71][72][73][74] in "thermal shallow-water modelling" of geophysical flows. Due to Pedro Ripa's investigation of its geometric structure and stability properties, [57][58][59][60]62 the core model has been known to many 10,43,52,65 as Ripa's model.…”
mentioning
confidence: 99%
“…However, these studies, as well as those using more complex numerical models and observations, have also shown that the eddy separation period can be modulated by external factors. Several studies emphasized the importance of the GoM inflows and outflows such as their relative magnitude (Pichevin & Nof, 1997;Weisberg & Liu, 2017;Moreles et al, 2021), their fluctuations (Oey et al, 2003;Sturges et al, 2010), their stratification (Moreles et al, 2021) and their vorticity (Candela et al, 2002;Oey, 2004). Vorticity was found to be modulated by mesoscale activity, such as cyclones in the GoM that can either block the invasion of the LC in the Gulf (Schmitz, 2005;Zavala-Hidalgo et al, 2006) or favor the release of LCE (Cheŕubin et al, 2006), as well as Caribbean Anticyclones (Murphy et al, 1999;Candela et al, 2002;Oey et al, 2003;Athieé t al., 2012;Garcia-Jove et al, 2016;Ntaganou et al, ), or deep eddies (Welsh & Inoue, 2000;Oey, 2008) that influence the dynamic of the LC.…”
Section: Introductionmentioning
confidence: 99%